2008
DOI: 10.1056/nejmoa0802944
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin versus Unfractionated Heparin during Percutaneous Coronary Intervention

Abstract: In patients with stable and unstable angina who underwent PCI after pretreatment with clopidogrel, bivalirudin did not provide a net clinical benefit (i.e., it did not reduce the incidence of the composite end point of death, myocardial infarction, urgent target-vessel revascularization, or major bleeding) as compared with unfractionated heparin, but it did significantly reduce the incidence of major bleeding. (ClinicalTrials.gov number, NCT00262054.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
203
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(228 citation statements)
references
References 27 publications
7
203
1
10
Order By: Relevance
“…Nawet do 20% pacjentów z NSTE--ACS nie ma zmian miażdżycowych lub są to zmiany niepowodujące zwężeń w obrębie tętnic wieńcowych. W przypadku pacjentów ze zwężeniami w obrębie tętnic wieńcowych 40-80% chorych ma wielonaczyniową CAD [164,224,303,304]. Niewydolność pomostów i choroba pnia lewej tętnicy wieńcowej mogą być przyczyną dolegliwości u odpowiednio 5% i nawet do 10% pacjentów z NSTE-ACS.…”
Section: Postacie Choroby Wieńcowejunclassified
See 1 more Smart Citation
“…Nawet do 20% pacjentów z NSTE--ACS nie ma zmian miażdżycowych lub są to zmiany niepowodujące zwężeń w obrębie tętnic wieńcowych. W przypadku pacjentów ze zwężeniami w obrębie tętnic wieńcowych 40-80% chorych ma wielonaczyniową CAD [164,224,303,304]. Niewydolność pomostów i choroba pnia lewej tętnicy wieńcowej mogą być przyczyną dolegliwości u odpowiednio 5% i nawet do 10% pacjentów z NSTE-ACS.…”
Section: Postacie Choroby Wieńcowejunclassified
“…Niewydolność pomostów i choroba pnia lewej tętnicy wieńcowej mogą być przyczyną dolegliwości u odpowiednio 5% i nawet do 10% pacjentów z NSTE-ACS. Zmiany w gałęzi przedniej zstępującej lewej tętnicy wieńcowej są najczęściej odpowiedzialne za niedokrwienie zarówno w STEMI, jak i NSTEMI-ACS (u nawet 40% pacjentów) [164,224,[303][304][305][306]. W obrębie tętnicy odpowiedzialnej za MI zmiany odpowiedzialne za niedokrwienie w NSTE-ACS częściej lokalizują się w obrębie proksymalnego i środkowego segmentu, z mniej więcej taką samą częstością w zakresie tych dwóch segmentów [305,306].…”
Section: Postacie Choroby Wieńcowejunclassified
“…Currently, bivalirudin is manufactured by Medicines Company (Parsippany, NJ, USA) at a cost of www.nature.com/aps Zhang DM et al Acta Pharmacologica Sinica npg approximately US$325 for a 250-mg vial [4] . Extensive investigations have confirmed that bivalirudin has several therapeutic features superior to UFH and LMWHs, including more predictable pharmacokinetics (PK) and pharmacodynamics (PD) behaviour, a lower proclivity to generate an immune response, and an equivalent suppression of acute ischemic events with fewer bleeding complications [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…There was a concern about a significant 1% increase in acute stent thrombosis seen within 24 hours, however, the rates for stent thrombosis at 30 days were similar in both groups. Bivalirudin was further examined in the REPLACE-2, ISAR-REACT 3, and ACUITY randomized trials evaluating patients across a broad spectrum of disease (stable CAD to high-risk ACS) undergoing PCI (92)(93)(94). The results of these trials solidified bivalirudin's favorable safety and efficacy profile when compared to UFH plus a GP IIb/IIIa inhibitor by demonstrating the non-inferiority of bivalirudin in preventing ischemic complications after PCI along with a reduction in rates of major bleeding.…”
Section: Direct Thrombin Inhibitorsmentioning
confidence: 99%